Effect of bupivacaine versus lidocaine local anesthesia on postoperative pain reduction in single-port access laparoscopic adnexal surgery using propensity score matching - Ji Hyun Lee; Sang Hyun Cho; Kyung Jin Eoh; Jung-Yun Lee; Eun Ji Nam; Sunghoon Kim; Sang Wun Kim; Young Tae Kim (Korean Society of Obstetrics and Gynecology, 2020)
ObjectiveThe umbilicus is a single, painful incisional site on the abdomen during trans-umbilical single-port access laparoscopic surgery. Previously, we found that periumbilical lidocaine could reduce postoperative pain. This study aimed to compare the efficacy of bupivacaine and lidocaine in reducing pain.MethodsWe performed a retrospective analysis in a study group (Bupivacaine group, 100 patients who received periumbilical infiltration of bupivacaine before their incisional site repair completion) and control group (Lidocaine group, 100 patients who received lidocaine at their incisional site repair completion). We compared postoperative pain based on the numerical rating scale (NRS) between propensity score-matched Bupivacaine-treated (n=50) and Lidocaine-treated (n=50) patients.ResultsThe postoperative pain scores based on the NRS were not significantly different between the 2 groups until 12 hours post-operation. However, 24 hours post-operation, the Bupivacaine group showed significantly lower pain than the Lidocaine group (24 hours, 1.76±1.07 vs. 2.53±1.11 NRS, P<0.001; 48 hours, 0.84±0.85 vs. 2.16±0.85 NRS, P<0.001).ConclusionPeriumbilical infiltration of bupivacaine has a longer acting efficacy on reducing postoperative surgical pain than that of lidocaine.